Analysis of Prognostic Factors in High-Grade Osteosarcoma of the Extremities in Children: A 15-Year Single-Institution Experience - Vasquez, Liliana; Tarrillo, Fanny; Oscanoa, Monica; Maza, Ivan; Geronimo, Jenny; Paredes, Gloria; Silva, Jose María; Sialer, Luis (Frontiers in Oncology, 2016)
Background: The aim of this retrospective study was to define clinical and pathologic features and prognostic factors among children and adolescents diagnosed with high-grade osteosarcoma of the extremities. Methods: A total of 73 patients younger than 18 years old diagnosed with primary osteosarcoma of the extremities between January 1998 and December 2013 were retrospectively evaluated. Prognostic factors such as age, gender, primary tumor site, alkaline phosphatase and lactate dehydrogenase levels, metastatic disease, pathological fracture, histological response and surgery type were analyzed to evaluate their effects on overall (OS) and event free survival (EFS). Results: At a median follow-up of 30 months (1.5-152), OS and EFS at 5 years was 64.5±8.1% and 48.5±8.7% for patients with localized disease; and 16.2±7.9% and 14.4±7.3% for patients with initial metastatic disease, respectively. In patients with localized disease, conservative surgery was performed on 22 of 46 patients (43.5%), and there was no significant difference in survival rates among patients who had conservative vs radical surgery (p=0.65). Although tumor size (>12cm) was significant prognostic factor in univariate analysis; multivariate analysis identified elevated levels of alkaline phosphatase (p=0.033) and poor response to neoadjuvant chemotherapy (p<0.001) only as independent prognostic factors. Age, histological type, pathological fracture and primary tumor site did not significantly affect prognosis. Conclusion: Initial elevated presence of alkaline phosphatase in serum and poor histological response after neoadjuvant chemotherapy were significant factors for unfavorable prognosis. It is necessary to optimize staging and treatment intensification to improve survival rates, especially among patients with metastasis at initial presentation.